If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2d+10=6d-d
We move all terms to the left:
2d+10-(6d-d)=0
We add all the numbers together, and all the variables
2d-(+5d)+10=0
We get rid of parentheses
2d-5d+10=0
We add all the numbers together, and all the variables
-3d+10=0
We move all terms containing d to the left, all other terms to the right
-3d=-10
d=-10/-3
d=3+1/3
| (v+1)^2=2v^2+11v+15 | | 3w-4=10 | | g(-8)=(-8+2)/3 | | 2b^2+18b+40=0 | | 24+3y=6 | | 13/(32x^2-18)=0 | | (7x-32)=(5x) | | 10p=20+6p | | 15x+18=12x+27 | | 2+13/4x=1/2+11/2x | | 7310=800s | | 25x²-144=0 | | 0.89x+72=1.69x | | 2^5x+1=8^x-1 | | .4x+15=x-16 | | 4v+2v=28 | | −13+x+5+6=5+4x−4 | | 5y^2-35y-40=0 | | -14=−7n | | x-1=3x+ | | 7+2n-6=9 | | 9/p=3/16 | | 16/18=3/n | | x-19/24x=40 | | 85+9x=15x+25 | | 1,2x^2+3,84x+177,69=0 | | 17.35=x+7.29 | | 3(6•3+7)=x | | w+75=-79 | | F(n)=3n+4^2 | | Y=x-4.Y=3x+4 | | 7(9+5x)=63 |